Pengaruh metode jarimatika dan metode sempoa terhadap kemampuan perkalian Mahasiswa PGSD Universitas Muhammadiyah Surakarta - Difansyah, Haikal Fikri; Apsari, Lukita; Zaki, Muhammad Nizar Ibnu; Novitasari, Putri; Aryanti, Vivin Putri (Nur Science Institute, 2024)
Learning mathematics is a teaching and learning process built by teachers to develop students' creative thinking and can improve the ability to construct new knowledge as an effort to improve good mastery of mathematical material. The purpose of learning mathematics is so that students are able and skilled in using mathematics. The research in this article aims to find out which method is more effective in increasing the multiplication ability of UMS PGSD students. The subjects of this study were PGSD UMS students. Data collection techniques in this study used tests in the form of post-test questions. The research results in this article show that the jarimatics method is more effectively used to improve multiplication skills than the abacus method.